NaCl Triggers the Sessile-to-Motile Transition of Bacillus subtilis - Prem Anand Murugan; Gupta, Manish Kumar; T Sabari Sankar; Chandran, Sivasurender; Matheshwaran, Saravanan (bioRxiv, 2022)
Various chemical cues are known to alter the motile and sessile states of bacteria differentially and, in turn, the formation of biofilms. However, the underlying mechanisms at the cellular and molecular level remain less understood, which severely limits our ability to control biofilms. Here, we systematically studied the effects of NaCl on the dynamics of biofilm formation across various length scales and the associated changes in the regulation of gene expression in an undomesticated natural isolate of Bacillus subtilis. Interestingly, NaCl induced significant changes in the architecture of pellicles and yielded systematic increase in lateral expansion rates of biofilms when grown on an agar surface. At the microscopic level, both in the presence and absence of NaCl, bacteria displayed super-diffusive motion at times lesser than a second. However, at larger delay times, we observed an intriguing NaCl-induced transition from sub-diffusion behavior of individual bacterial cells to rapid diffusion behavior. In addition, NaCl reduced the dynamical heterogeneity of the bacterial cells within the biofilm. The reduced heterogeneity and the increased flagellation in a subpopulation of cells in the presence of NaCl corroborates well with the observed higher motility of the cells. Further, the cellular uptake of NaCl resulted in the downregulation of several genes underlying the formation of biofilms, revealing the role of chemical cues like NaCl in controlling the gene regulatory circuit underlying the sessile to motile transition. Our study opens a new avenue to decipher the competitive advantage provided to the subcellular populations by NaCl due to lifestyle switch in Bacillus subtilis. Competing Interest Statement The authors have declared no competing interest.